Study on the Identification of Obstacle Paths for Digital Economy Promotion in Underdeveloped Regions based on ISM-MICMAC Modeling - He, Chuan; Tian, Yishai (Transactions on Economics, Business and Management Research, 2023)
Identifying the obstacles in the path of barriers to the promotion of the digital economy in less-developed regions can provide insight into the underlying causes that lead to the limited development of the digital economy. This helps the government and related organizations to formulate targeted policies and measures, which can be targeted to address the different barriers in solving the digital economy promotion problems and improve the development of the digital economy. A total of 26 influencing factors of barriers to the promotion of digital economy from six dimensions are categorized into three levels: surface, middle, and bottom according to the ISM model, and the influencing factors are categorized into three clusters of influencing factors, namely, independent, autonomous and connected, using the MICMAC method. The results of the study show that: (1) the digital divide factors such as the lack of digital economy professionals and the relatively weak economic foundation are the underlying factors hindering the promotion of the digital economy, and have the deepest impact on the obstacles in the path of digital economy promotion. (2) Inadequate education system, lack of government funding, and lack of related policy support are the linkage factors in the path of barriers to the promotion of the digital economy, with greater dependence and driving force, which need to be focused on.